The remarkable rain forest - Woods, Mae. (Edina, Minn. : Abdo Publishing, 1999)
Surveys the location, weather, products, plants, and animals of rain forests.
Includes index.
13
Keywords: Rain forests -- Juvenile literature; Rain forest ecology -- Juvenile literature; Rain forests